PENERAPAN APLIKASI WORDWALL dalam PEMBELAJARAN MATEMATIKA - Martono, Stefany Margareta; Kristina, Cindra (SOSCIED, 2024)
Mathematics is one of the compulsory subjects that students take at school. Mathematics is still something that is difficult for students to learn. For this reason, it is important to modify fun and interactive learning activities in the classroom with the use of applications. There are many applications that can be used to support mathematics learning activities. One application that can be used in wordwall. Wordwall is a teaching tool or media that teachers can use to make learning more interesting and interactive in the classroom. This Research was carried out at Cinta Kasih elementary School, Sorong City. Researchers carried out observations and guided teachers in using the wordwall application so that it was applied to grade 5 students. The research method used was quantitative research. This research was carried out with classroom action research planning, namely the researcher supervised the teacher in the learning process in the classroom using the wordwall application. Data collection in the form of data on student activity in the class in group, knowledge, skills. The research result show that students have an average score in the range of 76 – 79, which mean they are good at following the mathematics learning process in classwith the help of the wordwall application.